Corrosion Inhibition and Dye Studies of Mixed-Ligand Metal(II) Complexes: Synthesis and Characterization - Iyo, Israel Atamunotekeari; Festus, Chioma; Amadi, Jane Uchechi (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2025)
A new series of imine ligands and their M(II) complexes were synthesized via reflux from the aldol condensation of 2-hydroxy-1-naphthaldehyde and precursor 4 (C8H8N2S) and 6 (C5H7N3O) respectively. The FT-IR results showed ranges between 1667–1678cm-1 for the ligands and 1618–1658cm-1 for the M(II) complexes, indicating the formation of the azomethine group, and the coordination of the M(II) ions to the azomethine during complexation, hence, the longer band stretches. The bands 506–525 cm⁻¹ and 410–450cm-1 present in the M(II) complexes only, indicated M-O and M-N linkages, respectively. The UV-Vis bands 30960–50000 cm-1 and 26667–32467 cm⁻¹, respectively, indicated the presence of ????→????∗ and ????→????∗ of cyclic ring in the ligands and M(II) complexes. The solubility and thermal decomposition results showed that all compounds were insoluble in distilled H2O and were thermally stable at room temperature. At 303K the corrosion inhibition efficiency ranges 24.03–91.28% for the ligands, 60.92–98.65% for the metals, and at 373K the ranges 11.68–71.68% for the ligands, and 33.67–98.07% for the metals, showed that all the imine compounds possessed corrosion inhibition efficiencies governed by concentration, time and temperature, with the M(II) complexes showing better corrosion inhibition efficiencies. All imine compounds viably showed very-good to excellent dye properties on both natural and synthetic fabrics of wool, cotton, goat-hair and nylon, with color-fastness range 4–5 on the Standard Blue Scale. Hence, the mine compounds, possessing significant dyeing properties, are excellent alternative dyeing agents on textile fabrics.